What broke first? Characterizing sources of structural change prior to the great recession - Isaiah Hull (Sveriges Riksbank, 2015)
This paper identifies and characterizes episodes of structural change in the 27 years that preceded the Great Recession. This is done by performing Bai-Perron (2003a, 2003b) tests on 61,843 time series that span 34 countries, which collectively accounted for 81% of Gross World Product in 2013. Three major stylized facts are established. First, the rate of structural change increased throughout the early 1990s, stabilized in 2003, and then decreased slowly until 2007. Second, there were three large spikes in the pace of structural change after the 1990-1991 recession: 1993-1994, 2001-2003, and 2007-2009. The latter two overlap with recessions in the U.S. and many other major economies, but the first does not. This spike is associated with structural change in residential investment, consumption, exchange rates, and real estate. Across countries, the degree of structural change is highest in China during this episode. Third, the periods 1993-1994 and 1997-2000 contain heavy structural change in real estate and lending; however, the rate of structural change in house price and construction series was more pronounced in and after 2001.
Keywords: E30; E60; R20; C01; C59; 330; Great Recession; Macroeconomics; Econometrics; Break Tests; Structural Stability